Gender and generation in engagements with oil palm in East Kalimantan, Indonesia: insights from feminist political ecology - Elmhirst, R.; Siscawati, M.; Sijapati Basnett, Bimbika; Ekowati, D. (Informa UK Limited, 2017)
Across many parts of Indonesia, investment in oil palm has brought accelerated forms of land acquisition and market engagement for communities, signalling far-reaching implications for equity and well-being of current and future generations. This paper uses a conjunctural feminist political ecology approach to explore gendered and generational engagements with oil palm in Indonesia. The paper compares four communities in East Kalimantan that form part of an ongoing study of the gendered impacts of large-scale and independent smallholder investments in oil palm in the context of corporate zero deforestation commitments in West and East Kalimantan. We show how different pathways of engagement with oil palm – adverse or otherwise – reflect the interplay between modes of incorporation into oil palm systems with landscape history, gender, life stage and ethnic identity. Whilst our findings complicate singular 'victim' narratives, they also challenge the 'cruel optimism' that is accompanying the current oil palm boom.